Diagnostic delay of pyogenic vertebral osteomyelitis and its associated factors. (2nd January 2017) - Jean, M; Irisson, J-O; Gras, G; Bouchand, F; Simo, D; Duran, C; Perronne, C; Mulleman, D; Bernard, L; Dinh, A
Abstract : Objectives : Pyogenic vertebral osteomyelitis (PVO) is a rare disease with possible severe complications (e.g. sepsis and spinal cord injury). In the 1990s, diagnostic delay (DD) was often extensive as PVO has a non-specific clinical spectrum, mostly afebrile with back pain, and access to magnetic resonance imaging (MRI) was not straightforward. Our aim was to perform a new study focusing on the clinical spectrum and DD of PVO and its associated factors. Method : This study examined a prospective cohort of 88 patients having PVO with microbiological identification between 15 November 2006 and 15 November 2010. Results : The 88 patients included in the study (female:male ratio 1:8) had a mean age of 64.1 years. The mean (sd) DD was 45.5 (50.4) days (range 2–280), and 46 patients (52.2%) were febrile at diagnosis. The main microorganism involved was Staphylococcus (n = 45; 51.1%). In univariate and multivariate analyses, age > 75 years, antecedent back pain, involvement of bacteria, topography of PVO, and anti-inflammatory drug intake did not affect the DD, unlike a C-reactive protein (CRP) value > 63 mg/L or a positive blood culture (DD lowered from 73 to 17 days and from 90 to 30 days, respectively). Conversely, X-ray investigation was associated with a longer DD (from 14 to 34.7 days). Severity at diagnosis was not significantly different depending on the intake of anti-inflammatory drugs. Conclusions : Despite easier access to MRI, the DD for PVO remains long. One shortening factor is a high CRP value, which could be a useful diagnostic tool in case of back pain. Anti-inflammatory drugs seem to have no impact on DD and severity at diagnosis.